Analisis Hasil Belajar Biologi Siswa Kelas XII MIPA Pada Materi Pertumbuhan dan Perkembangan Berdasarkan Ranah Kognitif Taksonomi Bloom Revisi - Mila, Nor; Jumrodah; Fadillah, Az Zahro (Program Studi Pendidikan IPA, FKIP Universitas Pancasakti (UPS) Tegal, 2023)
This study aims to determine the analysis of biology learning outcomes for class XII MIPA students on growth and development material based on the cognitive domain of the revised bloom taxonomy using a descriptive method with a quantitative approach. Descriptive research aims to explain and describe the facts obtained in accordance with a certain point of view. The technique of determining the research subject was carried out by purposive sampling in which the research subjects were students of class XII MIPA MAS Muslimat NU. The results of the analysis of biology students found that the classification of evaluation questions for Biology class XII MIPA on growth and development material based on the cognitive domain of the Revised Bloom's Taxonomy already contains questions with an understanding indicator (C2) of 48% and an indicator of applying (C3) of 52%. The learning outcomes of class XII MIPA students based on the cognitive domain of the Revised Bloom's Taxonomy are that students are more able to solve questions with an understanding indicator (C2) of 80% compared to questions with an apply indicator (C3) of 63%.Keywords: revised bloom taxonomy, cognitive, analysis